Netverse: A Game-Based Learning Environment for Introductory Computer Networking - Neamsri, Kanphitcha; Arsanok, Purinprat; Vittayakorn, Sirion (My University, 2026)
This paper presents Netverse, a 3D game-based learning environment for introductory computer networking. It was designed to support hands-on learning of cable types and connections, network devices and ports, and IP-related concepts through puzzle-based interaction. The study had two objectives: to compare Netverse with Cisco Packet Tracer in terms of learning and retention, and to examine gameplay behavior and user experience in the game environment. In a pilot comparative experiment, 30 participants were randomly assigned to either Cisco Packet Tracer or Netverse and completed pre-test, immediate post-test, and delayed post-test measures. After the delayed post-test, all participants completed the GUESS questionnaire, and gameplay telemetry from Netverse sessions was analyzed. Both conditions improved learning outcomes; Netverse showed a larger unadjusted short-term total gain, with its clearest adjusted advantage in IP-related concepts, while showing comparable retention loss over two weeks. Gameplay log analysis revealed level-specific adaptation and repeated-correction patterns, and user experience ratings were positive overall. These findings suggest that Netverse shows promise as a game-based approach for introductory networking education.
Keywords: Computer networking education; Educational games; Game-based learning; Interactive 3D environment